Anti Dumping Code in International Trade Law in Relation to Unfair Trade Practices - Ukas Ukas; Lenny husna (International Journal of Sociology and Law, 2025)
The application of the Anti-Dumping Code in international trade law is the topic of discussion in this article. Particular attention is paid to what happens when unfair trade practices are involved. The primary focus is on addressing the issue of price discrimination in international trade, which frequently brings about negative consequences for developing nations like Indonesia. The article provides a description of the phenomenon of dumping, including its impact on domestic producers, as well as anti-dumping rules within the context of the GATT and WTO. This is accomplished through theoretical studies and normative analysis. In addition, it covers the difficulties that arise when putting anti-dumping legislation into effect, as well as the remedies that can be implemented to defend domestic markets from losses that are caused by dumping. The purpose of this article is to highlight the significance of international cooperation and domestic law amendments in order to maximize the effectiveness of the Anti-Dumping Code as an instrument for protecting fair trade.